2017
DOI: 10.1103/physrevlett.118.064301
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous High-Speed Recording of Sonoluminescence and Bubble Dynamics in Multibubble Fields

Abstract: Multibubble sonoluminescence (MBSL) is the emission of light from imploding cavitation bubbles in dense ensembles or clouds. We demonstrate a technique of high-speed recording that allows imaging of bubble oscillations and motion together with emitted light flashes in a nonstationary multibubble environment. Hereby a definite experimental identification of light emitting individual bubbles, as well as details of their collapse dynamics can be obtained. For the extremely bright MBSL of acoustic cavitation in xe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 34 publications
0
32
0
4
Order By: Relevance
“…It has also been shown that the lack of buoyancy enhances the energy concentration at the final stage of the bubble collapse [20], even for bubbles that are highly spherical and generally assumed not to be subject to deformation by gravity (maximum bubble radius R 0 ∼ 40 µm at atmospheric pressure). Bubbles collapsing with pronounced microjets in multibubble fields have been shown to emit less light (or none) compared to the spherically collapsing bubbles [21].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the lack of buoyancy enhances the energy concentration at the final stage of the bubble collapse [20], even for bubbles that are highly spherical and generally assumed not to be subject to deformation by gravity (maximum bubble radius R 0 ∼ 40 µm at atmospheric pressure). Bubbles collapsing with pronounced microjets in multibubble fields have been shown to emit less light (or none) compared to the spherically collapsing bubbles [21].…”
Section: Introductionmentioning
confidence: 99%
“…a) Blasenfeld, Bildbreite 2 mm. b) Kollision zweier leuchtender Blasen (von oben nach unten); Bildhöhe 300 µm, Bildabstand 200 µs (nach , American Physical Society 2017).…”
Section: Blasendynamik In Blasenwolkenunclassified
“…Immerhin gelang es unserer Gruppe in Göttingen kürzlich, bei der besonders hellen Vielblasen‐Sonolumineszenz von Xenon in konzentrierter Phosphorsäure mit einer sehr empfindlichen Hochgeschwindigkeitskamera, die Blitze und die Blasen gleichzeitig aufzunehmen (Abbildung ) . Dies bedeutet einen Fortschritt, denn wir können in den Blasenwolken eine Vielzahl von nichtsphärischen Blasenformen ausmachen, unter denen dennoch ein extrem heller Blitz entsteht.…”
Section: Blasendynamik In Blasenwolkenunclassified
See 1 more Smart Citation
“…It has also been experimentally shown that the secondary Bjerknes force favors the formation of bubble clusters instead of dendritic filament branches which alters the sonoluminescence intensity [49]. Thus, the study of multibubble dynamics may benefit sonochemical engineering applications where quenching of sonoluminescence is frequently encountered [29,50,51]. Moreover, the coupling between the individual bubbles in a collapsing bubble cloud may play an important role in the generation of shock waves and broadband cavitation noise [52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%